Halal violation episode: does severity and trust recovery impact negative consumption behavior? - Omar, NA; Zainol, Z; Thye, CK; Nordin, NA; Nazri, MA (Emerald Group Publishing Ltd, 2024)
Purpose - Managing trust recovery in case of violation of halal products should be seen in light of the severity of violation as perceived by the consumer. This study aims to investigate how the severity of violation on halal directly impact negative consumer behavior (avoidance, boycott and revenge), and its moderating effect on the relationship between trust recovery and avoidance, boycott and revenge. Design/methodology/approach - In total, 212 questionnaires were distributed amongst customers who were aware and/or had experienced the violation of a halal product in Klang Valley, Malaysia - each of whom were selected using convenience sampling methods. Data were analyzed using descriptive statistics and structural equation modelling techniques, were partial least squares (PLS) software was used to measure the direct and indirect relationships between the variables. Findings - The results of this investigation showed that trust recovery and negative consumer behavior are negatively related; severity is positively related to avoidance, boycott and revenge; and severity moderates the relationship between trust recovery and avoidance. Research limitations/implications - Empirically, it was found that severity and trust recovery are a significant component that influence negative consumption behavior. This study has significant implications alongside research implications despite some limitations. Practical implications - In a severe violation case, a company needs to ensure that the strategy to fix the problem is genuine and trustworthy, as consumer trust on the recovery action by company is significance to influence customer avoidance in consuming the company's product. Originality/value - The uniqueness of this study exists in the fact that it is the first known one to concentrate on halal violation and examine the moderating effect of severity of halal violation on the relationship between trust recovery and negative consumer behaviors (avoidance, boycott and revenge).